2019
DOI: 10.1038/s41467-019-10229-6
|View full text |Cite
|
Sign up to set email alerts
|

WASH phosphorylation balances endosomal versus cortical actin network integrities during epithelial morphogenesis

Abstract: Filamentous actin (F-actin) networks facilitate key processes like cell shape control, division, polarization and motility. The dynamic coordination of F-actin networks and its impact on cellular activities are poorly understood. We report an antagonistic relationship between endosomal F-actin assembly and cortical actin bundle integrity during Drosophila airway maturation. Double mutants lacking receptor tyrosine phosphatases (PTP) Ptp10D and Ptp4E, clear luminal proteins and disassembl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 67 publications
0
23
0
Order By: Relevance
“…This is mediated by Washout (Wash), a Wiskott-Aldrich Syndrome protein family member that activates the Arp2/3 complex thus allowing actin nucleation (Rottner et al, 2017; MacDonald et al, 2018). Wash has been studied in multicellular tubes of the tracheal system, but its role in terminal cell development has not been determined (Dong et al, 2013; Tsarouhas et al, 2019). We found that a UAS-Wash::GFP construct showed a strong, dynamic enrichment around CD4 vesicles (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This is mediated by Washout (Wash), a Wiskott-Aldrich Syndrome protein family member that activates the Arp2/3 complex thus allowing actin nucleation (Rottner et al, 2017; MacDonald et al, 2018). Wash has been studied in multicellular tubes of the tracheal system, but its role in terminal cell development has not been determined (Dong et al, 2013; Tsarouhas et al, 2019). We found that a UAS-Wash::GFP construct showed a strong, dynamic enrichment around CD4 vesicles (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Another essential process during wound healing is matrix remodeling. Interestingly, WASH was previously implicated in apical endocytosis of extracellular material in the Drosophila airway epithelium during embryogenesis (Tsarouhas et al ., 2019). Hence, WASH-ME could also contribute to matrix remodeling as a specialized mechanism for internalization of extracellular material.…”
Section: Discussionmentioning
confidence: 99%
“…The arrangement of the taenidial folds depends primarily on the interaction between endocytosis processes, apical actin formation, and the formation of the chitin-matrix at the apical cell surface. A disturbed taenidial fold arrangement is linked to tube collapse and gas-filling defects 57 59 . Our studies suggest that the formation of taenidial chitin requires Cht2.…”
Section: Discussionmentioning
confidence: 99%